Minorities in the Police Academy: Career Expectations of Female Police Cadets - Xu, Haoran (Women & criminal justice, 2025)
This study investigates the career expectations of female police cadets within the specific framework of the Chinese police academy system. Focused on their self-perceptions, this research aims to fill a gap in the literature concerning the experiences of female cadets during their training phase. Employing a qualitative approach, the study conducted focus group discussions with 56 female police cadets from diverse specializations and geographic regions. The findings indicate that, despite being a minority within the police academy, female cadets generally respond positively to the training and management strategies. The study reveals a notable shift in identity, with female cadets prioritizing their “police” identity over gender considerations. Additionally, concerns about career placement, competition, and societal expectations emerged, influencing their outlooks on future employment. This research contributes valuable insights into the complex interplay of gender dynamics and career expectations within the police academy context. The methodology and findings offer a foundation for further exploration of gender-related issues in law enforcement education, with implications extending beyond the borders of China.